Analisis Faktor Yang Mempengaruhi Pasangan Usia subur Dalam Pemilihan Kontrasepsi Suntik Kombinasi Dan Progestin Analysis Of Factors Affecting Fertile Couples Selection In Combined Injectable Contraceptive And Progestin - Sri Haryanti, Rusiana; - STIKES PKU Muhammadiyah Surakarta, Agsteria Alif’ta (IJMS - Indonesian Journal on Medical Science, 2017)
Abstract: Contraception is an attempt to prevent pregnancy. Acceptors are the most widely injectable contraceptive method (58.74%). Similarly, in a preliminary study in RB An-Nissa Surakarta found that most injectable acceptors (95.94%).This study aimed to determine the factors that influence the selection combined injectable contraception and progestin.The methods was a descriptive survey method. The population was Â all acceptors inject, Â many samples of 49 respondents. A sampling technique that accidental sampling. The instrument using a questionnaire, analysis of data frequency distributions. Results: factors and motivations most respondents chose Injectable combination of age-related reproductive age is 20-35 (80%), lifestyle (100%), the frequency of regular intercourse (96%), no complaints during intercourse ( 100%), birth control (84%), had been using contraception then stopped because I wanted to get pregnant again (71%). While on Injectable Progestin due to aging of reproductive age is 20-35 (76%), lifestyle (100%), the frequency of regular intercourse (90%), no complaints during intercourse (100%), birth control (88% ), have been using contraception then stop because they want to get pregnant again (62%), majority of the respondents chose a combination of injectable contraception because many health factors to menstruation (92%), for other health factors (100%). While on Injectable Progestin in many health factors to menstruation (82%), for other health factors (100%). Based on all respondents choosing a contraceptive method combined injectable contraception and progestin for reasons of contraceptive methods (100%). Conclusions: The factors that most influence the selection in injectable contraception and progestin combination contraceptive method is a factor.Keywords: Couple Childbearing Age, ContraceptivesÂ Abstrak: Kontrasepsi bertujuan untuk mencegah kehamilan. Akseptor KB yang paling banyak adalah metode kontrasepsi suntik (58,74%). Berdasarkan studi pendahuluan di RB An-Nissa Surakarta didapatkan akseptor KB terbanyak yaitu suntik (95,94%). Tujuan Penelitian ini untuk mengetahui faktor-faktor yang mempengarui PUS dalam pemilihan kontrasepsi KB suntik kombinasi dan progestin. Penelitian ini mennggunakan metode survey deskriptif. Populasinya adalah seluruh akseptor KB suntik di RB An-Nissa Surakarta, sampel 49 responden pada setiap kontrasepsi suntik. Teknik sampling menggunakan aksidental sampling. Instrumen yang digunakan adalah kuesioner, Analisis data menggunakan distribusi frekuensi. Hasilnya, faktor pasangan dan motivasi sebagian besar responden memilih KB Suntik kombinasi karena faktor usia reproduksi yaitu 20-35 (80%), gaya hidup (100%), frekuensi senggama teratur (96%), tidak ada keluhan saat bersenggama (100%), mengatur kehamilan (84%), sudah pernah menggunakan kontrasepsi kemudian berhenti (71%). Pada KB Suntik Progestin, faktor usia pada usia reproduksi yaitu 20-35 (76%), gaya hidup (100%), frekuensi senggama teratur (90%), tidak ada keluhan saat bersenggama (100%), mengatur kehamilan (88%), sudah pernah menggunakan kontrasepsi kemudian berhenti karena ingin hamil lagi (62%), Sebagian besar responden memilih kontrasepsi KB suntik kombinasi karena faktor kesehatan untuk menstruasi banyak (92%), untuk faktor kesehatan lainnya (100%). Sedangkan pada KB Suntik Progestin pada faktor kesehatan untuk menstruasi banyak (82%), untuk faktor kesehatan lainnya (100%). Kesimpulannya, faktor yang paling berpengaruh PUS dalam pemilihan kontrasepsi KB suntik kombinasi dan progestin adalah faktor metode kontrasepsi.Kata Kunci : Pasangan usia subur, Kontrasepsi